« L’Indépendance, c’est maintenant ! » Réflexion sur le soulèvement populaire en Algérie - Naoual Belakhdar (L’Année du Maghreb)
Since the 22nd of February 2019, Algeria is witnessing an unprecedented popular upheaval in its postcolonial history. Millions of Algerian citizens, from all genders, classes, ages and ideologies took to the streets across the whole national territory in order to oppose a 5th mandate of Abdelaziz Bouteflika and to ask for the departure of the entire system. If President Bouteflika’s resignation on April 2nd did not launch a proper transition democratic process, the most notable transformations are unfolding at the societal level. Drawing on fieldwork gathered through participant observation and formal and informal interviews with ordinary citizens who “became revolutionaries” in March and April 2019 in Algiers, Annaba and Ouargla as well as on the insights of social movement studies, this paper will reflect on the movement’s genealogy as well as on its links to previous mobilizations. The paper will also formulate first hypothesis as to the following questions: How are these events called by Algerian citizens? What kind of imaginaries are carried by the slogans and demands expressed throughout the different types of mobilisations? What kind of transformations have been launched at the level of the subjectivities and the collective level? And finally: what are we witnessing? Should this movement be read only through the lens of Algeria’s political history or as a moment in the cycle sparked by the Arab upheavals in 2011?